Communication—Reduction of DC Resistance of Ni-Rich Lithium Transition Metal Oxide Cathode by Atomic Layer Deposition. Issue 4 (1st April 2021) - Shi, Yang; Xing, Yingjie; Kim, Kitae; Yu, Taehwan; Lipson, Albert L.; Dameron, Arrelaine; Connell, Justin G.
Abstract : A coating using Atomic layer deposition (ALD) of Al2 O3 was applied to Ni-rich lithium transition metal oxide cathode material. This ALD coating reduces the DC resistance (DCR) and increases the cycling performance of the Ni-rich cathode. The reduced DCR comes from decreased solid electrolyte interphase (SEI) resistance on the anode, which is attributed to reduced transition metal deposition. This is due to the ALD coating preventing the direct contact between the cathode and the electrolyte, and therefore inhibits transition metal dissolution. This study suggests the promise of using ALD coating to reduce the DCR of Ni-rich cathode materials.